Impact of Music Therapy on Pain, Stress, and Physiological Parameters Among Postoperative Patients - C Cecyli; R Vasika; J Jagadeeswari; A Priyadarsini; BAA Dayana (Wolters Kluwer Medknow Publications, 2024)
Introduction: Post-surgery acute pain is often uncontrolled, causing significant harm to patients, despite improvements in pain management. Music therapy can help to reduce physiological and psychological stress, making it a valuable tool for stress and pain Alleviation. Objectives: To evaluate the effectiveness of music therapy on pain, stress, and physiological parameters among postoperative patients. Methods: With 60 samples that matched the inclusion criteria, a quasi-experimental pretest and posttest study methodology was used. Before the music intervention, after the postoperative day 0, and after the intervention on the 7th postoperative day, the physiological parameters for both groups were collected together with the pain score and stress level using a Numerical Rating scale (NRS) and Perceived Stress Scale. Both descriptive and inferential statistics have been used for the data. Result: In comparison to the control group, there was a significant decrease in the study group's mean scores for pain and stress, and found significant changes in physiological variables such as pulse rate, SPO2, respiration rate, and systolic and diastolic BP. Conclusion: Among postoperative patients, music was found to have positive effects on pain, stress, and physiological markers.